Educação ambiental e áreas verdes urbanas: os vínculos e as relações afetivas em processos educativos em uma microbacia em urbanização - Figueiredo, Andréia Nasser (Universidade Federal de São Carlos, 2018)
Seeking to work in a contextualized way a critical environmental education in urban area, we immerse ourselves in a study about the relations established by human beings with other beings in green spaces. We believe that these spaces are spaces allow, besides the existence and the conviviality of human beings with other beings, the education of relationships continuously and mainly through the education of attention. Based on the paradigm of phenomenology, the objective of the present work was to identify the relations that guide the look and live in urban spaces of people-other beings (human or not) seeking the feelings, sensations, emotions and motivations expressed by people, that interweave them to urban green places. The city of São Carlos, in the interior of the state of São Paulo, was chosen because it presents a context of revision of the Master Plan of the municipality and a history of mobilizations in favor of green spaces. We collect data with two distinct groups of people in two different processes. The first group was formed by 14 people participating in a university extension project. Using education of attention, dialogical practice and aiming at the formation of values the course of extension of environmental education and urban green areas was developed over eight months. Individual and collective materials were produced in this process and later analyzed by us. The second group participating in the research was formed by eight people engaged in the maintenance of urban green spaces. All the participants were residents of the same area where the extension course of the first group had been held. We selected this area because it is one of the discussion areas of the Master Plan because it is predicted to urban growth. We conducted interviews with the walking interview methodology as a way to expand the collection of data related to these people's relationships with the green spaces. From the statements and reports generated, we selected the parts that instigated us for analysis and reflection. Three articles with the selected data were produced. The first one with the data from the student group gave us the elements to understand how a practice of attention education can prioritize the work with values and place them as the founding element of our choices, actions and (re) choices. The second article, with the data of the group of dwellers allowed us to delve into relationships established throughout a continuous education through the flow of life. And the third article, using data from both groups, allowed us to understand the power of working environmental education in urban green areas. All the participants came together to reinforce the urgency of revising the building of values established in our society. To understand ourselves as collectives, to understand ourselves in knowing the other (human or not), to respect existences, to keep continuous the practices and actions that allow a return to relationships were poignant in our reflective process. Finally, we reinforce here the role of a critical educational practice, dialogical and in search of more equal relations within a historically exclusive urban space.
Keywords: Educação da atenção; Espaços verdes urbanos; Valores éticos e estéticos; Education of attention; Urban green spaces; Ethical and aesthetic values; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS HUMANAS::EDUCACAO